A case of necrotizing crescentic glomerulonephritis with arteritis due to secondary amyloidosis following rheumatoid arthritis - SUYAMA, Katsuo; WATANABE, Mitsumasa; NOGAKI, Fumiaki; MUSO, Eni; KAMATA, Tadashi; OYAMA, Atsushi; ONO, Takahiko; KAWAMURA, Takahide; SAKURAI, Mani; SASAYAMA, Shigetake (Nihon Jinzo Gakkai shi, 1997)
A 47-year-old woman was admitted on because of edema of the lower extremities.She had been suffering from RA for about 20 years and underwent total kneereplacements 5 years previously. On admission, nephrotic syndrome and rapidly progressive glomerulonephritis had developed in association with ileus, melena, diarrhea, dyspnea and hemoptysis. She showed a high titer of serum rheumatoid factor (357.0IU/ml) and amyloid A protein (83.9μg/ml) with positive antinuclear antibodies (homogeneous and speckled patterns). However, anti -neutrophil cytoplasmic autoantibody (ELISA), immune complexes and anti -glomerular basement membrane antibody (ELISA) were negative. Renal biopsy showed microscopic PN overlapping A-type positive amyloidosis. Although the maintenance of hemodialysis was necessary, aggressive immunosuppressive therapy with steroid pulse therapy and frequent plasma exchange provided a rapid improvement of systemic symptoms possibly due to vasculitis. We suggested that in this case, massive necrotizing crescentic glomerulonephritis with systemic arteritis developed on the basis of secondary amyloidosis due to rheumatoid arthritis. In such a case, even if various serum autoantibodies and immune complexes were negative, plasma exchange was suggested to be effective to remove not only pathogenic autoantibodies but also various serum inflammatory cytokines which may be related with severe vasculitis and glomerulitis, in addition to aggressive steroid therapy which may suppress the invasion of inflammatory cells producing these cytokines.